1989
DOI: 10.2307/3899479
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Native Shrubs on Nutritional Status of Goats: Nitrogen Retention

Abstract: In viva digdbiiity trials were conducted to evaiuate the infhtence of shrubs contafning low and high ieveis of soluble pbenoiic/tannins on dig-and nitrogen retention by Angora goats. Each of 6 shrubs and alfaG hay (M&ugo sutiva L.) were fed to goats at 30% (dry matter b&s) of the diet in 8 bariey straw-pr&ie bay mixture. Tbe mixture was reguiated so that ali diets contained about 8% crude protein. High soluble pl~enotic shrubs used included big sagebrush (Artemi.du-Nutt. ssp. &i&&da), gray oak (Querc~~ grireu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 15 publications
5
17
1
Order By: Relevance
“…The net effect of tannins was thus minor. Such perspectives have been reported elsewhere (Nastis and Malechek, 1981;Tanner, 1988;Woodward, 1988;Nunez-Hernandez et al, 1989).…”
Section: Photograph: Shewangizaw Bekelesupporting
confidence: 77%
“…The net effect of tannins was thus minor. Such perspectives have been reported elsewhere (Nastis and Malechek, 1981;Tanner, 1988;Woodward, 1988;Nunez-Hernandez et al, 1989).…”
Section: Photograph: Shewangizaw Bekelesupporting
confidence: 77%
“…Nuňez-Hernandez et al (1989) observed similar DM intakes for Angora goats on a diet containing a high tannin shrub (Juniperus monosperma) compared with goats fed an alfalfa hay diet. Other studies have indicated that plant secondary metabolites (PSM) such as tannins may reduce DMI of forage legumes by decreasing palatability (Reed, 1995).…”
Section: Discussionmentioning
confidence: 74%
“…D. Dearing, personal observations). Juniper has notable levels of PSCs, particularly terpenes and, to a lesser extent, phenolics (Adams et al 1981;Nú ñez-Hernández et al 1989). The limited amount of juniper that N. albigula can consume is largely dictated by PSCs and not nutrient content (Dearing et al 2000;Sorensen et al 2005b).…”
Section: Introductionmentioning
confidence: 99%